Integrated Versus Traditional Method in Basic Medical Science Education: A Comparative Study in an Indian Medical College - Pokhrel, Rishi; Tandon, Aseem; Bhatnagar, Rajan (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Medical education is at crossroads with various approaches in use throughout the world. Many medical schools in developing countries are on the verge of transition from traditional didactic lecture based approach to a problem-based approach. This study was conducted to evaluate the efficiency and efficacy of horizontal integration in comparison to isolated didactic lectures. Methods: This study was conducted at an Indian Medical college where integration is not routinely practiced. Lectures of anatomy and physiology were integrated and students’ understanding was assessed using pre-test and post-test in the form of 10 multiple-choice questions each. Opinion of students was taken using a questionnaire. Total students participating in the study were 118. Results: The mean score in pretest was found to be 5.32±1.88 and mean post-test score was 5.43±1.89. Students t test revealed a P value of 0.65 reflecting no statistically significant difference in the results. In the subjective assessment 76% of students didn't have any past experience of integration of 2 difference subjects, 87% students said that integration of anatomy and physiology lectures facilitated the understanding of the subject, 75% students wanted more topics to be taught in an integrated manner in future whereas 23% students say that only few relevant topics should be integrated. 47% of students recommended the integration of more subjects and the subject chosen was biochemistry. Most students said that such integration provided a better and holistic understanding of topics being covered. Students identified no disadvantages of integration. Conclusions: The objective result showed no significant improvements in scores of pre-test and post-test. On the other hand the subjective response of the students pointed towards an integrated approach being superior to stand alone didactic lectures in providing better understanding.